The Economics of Patent Backlog - Alexandra Karin Zaby; Gaétan de Rassenfosse (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Patent offices around the world face massive backlogs of applications, which threatens to slow down the pace of technological progress. However, economists lack analytical tools to address the issue. This paper provides a model of patent backlog inspired from the traffic congestion literature. Inventors in the cohort are heterogeneous with respect to desired patent pendency duration and react in anticipation of the waiting time resulting from the backlog. They can accelerate or slow down pendency duration by adapting their filing strategy. We find that the backlog impedes patent examination progress by providing incentives to strategically manipulate pendency. We discuss four policy responses: increasing examination capacity; introducing a penalty fee; altering the value of pending applications; and allowing deferred examination.
Keywords: O34; R48; O38; 330